2001
DOI: 10.1073/pnas.141125098
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-specific regulation of the ribosome– translocon junction by N-terminal signal sequences

Abstract: Amino-terminal signal sequences target nascent secretory and membrane proteins to the endoplasmic reticulum for translocation. Subsequent interactions between the signal sequence and components of the translocation machinery at the endoplasmic reticulum are thought to be important for the productive engagement of the translocon by the ribosome-nascent chain complex. However, it is not clear whether all signal sequences carry out these posttargeting steps identically, or if there are differences in the interact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
75
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 38 publications
14
75
0
Order By: Relevance
“…We have also observed that deletion of the signal peptide prevents translocation, resulting in cytosolic molecules that are fully accessible to added protease. This result, which confirms other published reports (8,10), indicates that the hydrophobic, transmembrane segment cannot by itself target the polypeptide chain to the translocon. Thus, in contrast to the case for other type II membrane-spanning proteins (whose N termini are cytoplasmic), the transmembrane domain of PrP is not capable of functioning as a signal-anchor sequence.…”
Section: Topological Determinants In Prprelative Amount Ofsupporting
confidence: 92%
“…We have also observed that deletion of the signal peptide prevents translocation, resulting in cytosolic molecules that are fully accessible to added protease. This result, which confirms other published reports (8,10), indicates that the hydrophobic, transmembrane segment cannot by itself target the polypeptide chain to the translocon. Thus, in contrast to the case for other type II membrane-spanning proteins (whose N termini are cytoplasmic), the transmembrane domain of PrP is not capable of functioning as a signal-anchor sequence.…”
Section: Topological Determinants In Prprelative Amount Ofsupporting
confidence: 92%
“…Analysis of the state of the ribosome-translocon junction (Fig. 4B) was exactly as described (16). For puromycin analysis (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Beyond merely stimulating the initiation of translocation, signal sequences can regulate the association between the ribosome and translocon and the exposure of the nascent chain to the cytoplasm or ER lumen (13)(14)(15)(16). In at least one case, that of the prion protein, the consequence of this regulatory step is the governance of the final topology achieved by the protein (13)(14)(15)(16)(17). These observations raise the possibility that signal sequences have a broad post-targeting role beyond the initiation of translocation, and in addition to their role in regulating the ribosome-translocon association.…”
mentioning
confidence: 99%
“…Moreover, the extent to which TM proteins in general and polytopic proteins in particular can adopt transient and reversible topologies at the ribosometranslocon interface during translocation at the ER remains to be established (Goder et al, 1999;Heinrich et al, 2000). Dynamic interactions between potential TM segments and between these segments and a signal peptide, when present, may influence final topology, resulting in interdependent insertion (Monne et al, 1999;Rutkowski et al, 2001). In addition, the extent to which the apparent unique insertion orientations usually observed in vivo result from proteolytic destruction of alternate topological forms by the quality control machinery of the ER (Schubert et al, 2000;Travers et al, 2000) also remains to be better defined.…”
Section: Introductionmentioning
confidence: 99%